Implementasi Model Pembelajaran Discovery Learning Terhadap Motivasi Belajar Siswa Kelas VII Pada Mata Pelajaran Fikih Di MTs Al-Misbah Sucinaraja Kab. Garut - Salamudin, Ceceng; Julian, Alvin (STAI Al-Musaddadiyah Garut, 2022)
This study is motivated by the observed low learning motivation among students, which is evident from their inadequate understanding of Fiqh subjects. The Discovery Learning model is proposed as a potential solution to this issue, as it allows students to explore new concepts and discover answers to the problems they encounter. This approach fosters intrinsic motivation to learn by encouraging students to independently construct their understanding. The purpose of this research is to describe the implementation of the Discovery Learning model and its impact on the learning motivation of seventh-grade students in Fiqh classes at MTs Al-Misbah Sucinaraja, Garut Regency. This field research employs a qualitative descriptive method. The primary data sources include factual information obtained from Fiqh teachers, seventh-grade students, school management, and other relevant informants. Secondary data sources consist of books, journals, school documents, and other written materials. Data were collected through observation, interviews, and document analysis. The data analysis technique employed is content analysis, involving data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the implementation of the Discovery Learning model has successfully enhanced the learning motivation of seventh-grade students in Fiqh subjects at MTs Al-Misbah Sucinaraja. This success is reflected in the improved cognitive performance seen in end-of-semester assessments, as well as in the affective and psychomotor evaluations demonstrated by students' attitudes, active participation in learning activities, and engagement in extracurricular activities. Notably, many students from MTs Al-Misbah Sucinaraja have participated in religious competitions, highlighting the broader impact of increased motivation facilitated by the Discovery Learning model. In conclusion, the implementation of the Discovery Learning model effectively boosts students' motivation to learn. Keywords: Discovery Learning Model, Student Learning Motivation, Fiqh Subject